Statistical data analyses to elucidate the causes and improve the countermeasures for preventing train accidents in Japan - Miwa, Masahi (Animo Repository, 2006)
We investigate train accident data in Japan to elucidate the causes and improve the countermeasures for reducing the number of train accidents. We deal with statistical data on train accidents in the last 15 years, including frequency, types such as derailment and crash, causes and consequences. We review the historical trend of train accidents by applying a statistical modeling approach dealing with both serious accident data and total number of accidents. Probability distributions for explaining this train accident data are shown. We show the results of quantitative data analyses on the train accidents, that occurred at the ground-level crossing and the relationship among utility type of railway company, equipment at the crossing and consequences of the accidents. Probabilistic mathematical models are used in the analyses. Finally, we try to evaluate the effectiveness of the countermeasures for preventing train accidents.